Applied Barcoding: The Practicalities of DNA Testing for Herbals - Caroline Howard; Claire Lockie-Williams; Adrian Slater (Plants, 2020)
DNA barcoding is a widely accepted technique for the identification of plant materials, and its application to the authentication of commercial medicinal plants has attracted significant attention. The incorporation of DNA-based technologies into the quality testing protocols of international pharmacopoeias represents a step-change in status, requiring the establishment of standardized, reliable and reproducible methods. The process by which this can be achieved for any herbal medicine is described, using Hypericum perforatum L. (St John’s Wort) and potential adulterant Hypericum species as a case study. A range of practical issues are considered including quality control of DNA sequences from public repositories and the construction of individual curated databases, choice of DNA barcode region(s) and the identification of informative polymorphic nucleotide sequences. A decision tree informs the structure of the manuscript and provides a template to guide the development of future DNA barcode tests for herbals.